'Alexa, was Buddha Born in Nepal?': microcelebrity, citizenship, and digital diaspora on YouTube. Issue 1 (2nd January 2023) - Dennis, Dannah
ABSTRACT: The claim that 'Buddha was Born in Nepal' is pervasive in contemporary discourses about Nepali national identity. This article focuses on the ways in which the claim to Buddha's birthplace is deployed by some Nepalis living beyond Nepal as both a means of maintaining a connection to Nepal as a diasporic homeland and as a means of building their own online celebrity. In particular, I analyse how the claim is communicated online by three Nepali YouTubers (Lex Limbu, James Shrestha, and Sagar Tamang), whose videos embed the claim to Buddha's birthplace within recognizable genres, memes, and narratives that are part of the Internet's shared culture. I argue that the makers of these videos are not only reaffirming their own sense of connection to Nepal as their diasporic homeland, but are also building their own personal brands by linking their own reputations as digital microcelebrities with the Buddha's global name recognition. Through this case study, I aim to theorize how microcelebrity can be a form of practicing citizenship at a distance within the context of a digital diaspora.